Black holes in superstring theory: thermodynamic stability of five dimensional black holes in heterotic brane-worlds (2010)
In Superstring Theory, analogous objects to classical (non-quantum) Black Holes may appear as the result of considering the superposition of massive D-branes. The similarity of these objects with classical Black Holes has lead to the definition of microscopic quantities that resemble entropy, area and other geometrical characteristics that these objects possess. Since Superstring Theories are presumed to have information on quantum gravitational phenomena, the analysis of these properties is crucial for understanding the microscopic structure of Black Holes. Like for classical Black Holes, for Superstring Theory Black Holes there exist several solutions depending on the conditions imposed on the brane-world action. The aim of this project is to analyze the thermal stability/instability conditions for Black Holes that appear in Heterotic Superstring Theory. That is, starting from the general free action, in ten dimensions, and considering the coupling to external fields (such as Maxwell Fields), get the solutions of the induced metric on the world-sheet and analyze the behavior of the solutions, for variations of parameters such as mass, charge, angular momentum, metric and other fields, thus reaching a conclusion as to which conditions give thermodynamic stability, if any.